2017
DOI: 10.1097/mpg.0000000000001662
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of New Colombian Food-based Complementary Feeding Recommendations Using Linear Programming

Abstract: The present study demonstrated the value of using LP to adapt NCFg for a different age group than the one for which they were designed. Our analyses suggest that to ensure dietary adequacy for 12- to 23-month olds these adaptations should include legumes, dairy products, vitamin A-rich vegetables, organ meat, and a fortified food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
(33 reference statements)
0
13
0
Order By: Relevance
“…In the context of severe malnutrition, it was shown that no combination of local foods was able to achieve a nutrient density as high as diets promoted by the WHO, thus showing the need for fortified foods in this specific health condition ( 70 ). Several others studies have found that nutritional adequacy was only attainable via the inclusion of fortified products ( 47 , 48 , 69 ). For example, in Kenya, with no zinc-fortified water, only 76% of the zinc RVs could be covered in the nutritionally best diet for young children, which was improved to 101% with the fortified product ( 48 ).…”
Section: Nutritionally Adequate Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of severe malnutrition, it was shown that no combination of local foods was able to achieve a nutrient density as high as diets promoted by the WHO, thus showing the need for fortified foods in this specific health condition ( 70 ). Several others studies have found that nutritional adequacy was only attainable via the inclusion of fortified products ( 47 , 48 , 69 ). For example, in Kenya, with no zinc-fortified water, only 76% of the zinc RVs could be covered in the nutritionally best diet for young children, which was improved to 101% with the fortified product ( 48 ).…”
Section: Nutritionally Adequate Dietsmentioning
confidence: 99%
“…Iron, zinc, and calcium were common problem nutrients in children aged 6–23 mo living in Indonesia ( 68 ), in 5 Southeast Asian countries ( 47 ), and in Kenya ( 42 , 43 ), whereas vitamin A and zinc were problematic for Kenyan children aged 4–6 y ( 48 ). Thiamin was identified as the only “problem nutrient” for a population of children from Bogota (Colombia) aged 12 mo ( 69 ). When nutrient gaps remain with locally available food sources, there is evidence for advocacy to modify the food supply in order to reach nutritional adequacy.…”
Section: Nutritionally Adequate Dietsmentioning
confidence: 99%
“…Optifood allows users to identify population-specific dietary nutrient gaps and develop food-based recommendations (FBR) centered on locally available and acceptable foods, accounting for existing dietary patterns and economic feasibility [14]. In addition, the approach can be used to evaluate the ability of existing and novel nutrient supplements and fortified foods to meet population-specific nutritional requirements [15,16,17,18,19], although it has, to date, primarily been used for infants and young children.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study that has investigated the sensitivity of FBR and of identified problem nutrients to the selection of dietary intake data, criteria and energy and fat requirements by linear programming. The sensitivity of the results of linear programming to the model input data is often mentioned, but rarely quantified [9,23,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity of the developed FBR and of identified problem nutrients to these choices is often described only in general terms in the discussion of papers using linear programming [9][10][11][12][22][23][24][25][26], but rarely quantified by sensitivity analysis [9,23,25,26]. It is therefore unknown what effect the choice of dietary intake data, selection criteria and energy and nutrient requirement data have on the final results of linear programming.…”
Section: Introductionmentioning
confidence: 99%